Corrosion protection of the reinforcing steels in chloride-laden concrete environment through epoxy/polyaniline–camphorsulfonate nanocomposite coating. (January 2015) - Pour-Ali, Sadegh; Dehghanian, Changiz; Kosari, Ali
Highlights: Epoxy/polyaniline–camphorsulfonate nanocomposite coating well protects steel rebar. Coating performance is evaluated by impedance measurements up to 1 year. Ultimate bond strength between the coated rebars and concrete is measured. Self-compacting concrete shows better anticorrosive property compared to normal one. Abstract: In this study, an epoxy/polyaniline–camphorsulfonate nanocomposite (epoxy/PANI–CSA) is employed to protect reinforcing steels in chloride-laden concrete environment. The synthesized nanocomposite was characterized using Fourier transform infrared spectroscopy and transmission electron microscopy. Bare, epoxy-coated and epoxy/PANI–CSA nanocomposite-coated steel rebars were embedded in normal and self-compacting concretes. To evaluate their corrosion behaviors, open circuit potential and impedance measurements were performed for the duration of 1 year. Ultimate bond strength of concrete with the reinforcement bars were measured in corroded and uncorroded conditions. It was found that epoxy/PANI–CSA coating provides good corrosion resistance and durable bond strength with concrete for steel rebars.